2001
DOI: 10.1046/j.1365-2249.2001.01692.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukaemia cells secrete a soluble factor that inhibits T and NK cell proliferation but not cytolytic function – implications for the adoptive immunotherapy of leukaemia

Abstract: SUMMARYEvidence of an immune mediated graft-versus-leukaemia effect has led to the belief that T and NK cell based adoptive immunotherapy can constitute effective treatment for relapsed leukaemias. However, work on solid tumours has shown this strategy may be hampered, by an immune escape mechanism in which tumour secreted immunosuppressive factors compromise T and NK cell function. Indeed, acute myeloid leukaemia (AML) cells secrete immunosuppressive factors that block the synthesis of Th1 type cytokines in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 42 publications
2
52
1
Order By: Relevance
“…Release of immunosuppressive cytokines, impaired NK cell-mediated cytotoxicity and IFN-g secretion Altered CD137-CD137L expression 46 Increased NK cell CD137 (CD137L expression is related to monocytic differentiation) Impaired cytotoxicity and IFN-g secretion Release of immunosuppressive cytokines Increased AML cell CD137L High AML cell CD200 expression 47 Reduced frequency of activated NK cells, dull NCR profile Impaired NK cell-mediated cytotoxicity and IFN-g secretion Secretion of soluble immunosuppressive factors For example, TGF-b 51 and IL-2R 48,50,108 Inhibition of NK cell proliferation 109 and cytotoxicity 49,51 Resistance of AML cells to killing Defects in apoptosis mechanisms, [52][53][54] resistance to TRAIL and Fas-mediated killing by high decoy 58,59 or low receptor expression [55][56][57] Impaired NK cell-mediated cytotoxicity activating and inhibitory signals tipping over towards the former. As mentioned before, signaling is relayed through a variety of NK cell activating and inhibitory receptors following ligation (depicted in Figure 2).…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
“…Release of immunosuppressive cytokines, impaired NK cell-mediated cytotoxicity and IFN-g secretion Altered CD137-CD137L expression 46 Increased NK cell CD137 (CD137L expression is related to monocytic differentiation) Impaired cytotoxicity and IFN-g secretion Release of immunosuppressive cytokines Increased AML cell CD137L High AML cell CD200 expression 47 Reduced frequency of activated NK cells, dull NCR profile Impaired NK cell-mediated cytotoxicity and IFN-g secretion Secretion of soluble immunosuppressive factors For example, TGF-b 51 and IL-2R 48,50,108 Inhibition of NK cell proliferation 109 and cytotoxicity 49,51 Resistance of AML cells to killing Defects in apoptosis mechanisms, [52][53][54] resistance to TRAIL and Fas-mediated killing by high decoy 58,59 or low receptor expression [55][56][57] Impaired NK cell-mediated cytotoxicity activating and inhibitory signals tipping over towards the former. As mentioned before, signaling is relayed through a variety of NK cell activating and inhibitory receptors following ligation (depicted in Figure 2).…”
Section: How Aml Evades Nk Cell Immune Surveillancementioning
confidence: 99%
“…3,4 The ability of AML blasts to remain protected from the graft-versusleukemia effect has been incompletely studied to date. [5][6][7] In this study, we elucidate the mechanisms by which AML blasts hamper immune responses by demonstrating that secretion of arginase II from AML blasts significantly affects T-cell proliferation and polarizes monocytes toward an immunosuppressive M2-like phenotype. In addition, the increased arginine metabolism inhibits the proliferation of hematopoietic progenitors, contributing to a wider suppressive microenvironment in AML.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, multiple deficiencies of T-and NK-cell functions, with ensuing relapse risk and poor prognosis, have been observed in patients with AML who did not undergo transplantation. [14][15][16][17][18] In earlier studies, investigators demonstrated that nonmalignant phagocytic cells down-modulate lymphocyte functions by producing and releasing NADPH oxidase-derived reactive oxygen species (ROS). [19][20][21][22][23] These findings have formed the basis for the use of a NADPH oxidase inhibitor in conjunction with IL-2 as a relapsepreventive strategy in patients with AML.…”
mentioning
confidence: 99%